The Effect of Adding Water Hyacinth (Eichhornia crassipes) Fermented with Aspergillus niger in Feed on Protein Retention of Tilapia (Orechormis niloticus) - Syavira Azzahra; Firdus Firdus; Lenni Fitri (Postgraduate, University of Mataram, 2025)
Feed is one of the important factors in fish farming, because it can account for 60–70% of the total operational costs of cultivation. The purpose of this study was to analyze the effect of providing water hyacinth (Eichhornia crassipes) fermented with Aspergillus niger as feed on the growth performance of tilapia (Oreochromis niloticus). This study used an experimental method and a Completely Randomized Design (CRD) consisting of five treatments and three replications, with the composition of P0 (commercial pellets) as the control, P1 (30% unfermented water hyacinth flour), and P2 (10%), P3 (20%), and P4 (30%) fermented water hyacinth flour. The results of this study showed that the addition of water hyacinth flour fermented with Aspergillus niger had no significant effect (P > 0.05) on tilapia protein retention. It was also known that the water quality in the tilapia maintenance media was within the optimal range.